Peran dan Fungsi Keluarga Dalam Islam - Wirda Wiranti Ritonga (Medan Resource Center, 2021)
This study examines the role and function in the family according to Islam. The purpose of this study is to recognize, learn, and discuss the roles and functions that the head of the family must carry out for his family members. In Islam, the family has an important meaning where the family is part of the Islamic society and it is in the family that one learns about Islam from childhood. Family in Islam is a household that is built from a marriage between a man and a woman which is carried out according to Islamic religious law that meets the requirements of marriage and the existing pillars of marriage.